IMMUNOHISTOCHEMICAL CHARACTERISTICS OF UTERINE STROMAL SARCOMA - Umida A. Qalandarova ,; Bahrom S. Yuldashev , (Central Asian Journal of Medicine, 2025)
For immunohistochemical study of malignant mesenchymal tumors of the uterus, 26 patients with uterine stromal sarcoma and 24 patients with uterine leiomyosarcoma were selected. In addition to the results of the morphological study, the expression of cells with monoclonal antibodies VEGF, Ki67 and Bcl 2 was studied using the Bond Leica Australia (Australia) immunohistoprocessor for immunohistochemical research, which is currently recognized as the gold standard in the world.